Source–Receptor Relationship Analysis of the Atmospheric Deposition of PAHs Subject to Long-Range Transport in Northeast Asia - Inomata, Yayoi; Kajino, Mizuo; Sato, Keiichi; Kurokawa, Junichi; Tang, Ning; Ohara, Toshimasa; Hayakawa, Kazuichi; Ueda, Hiromasa (Environmental science & technology, 2017)
The source–receptor relationship analysis of PAH deposition in Northeast Asia was investigated using an Eulerian regional-scale aerosol chemical transport model. Dry deposition (DD) of PAH was controlled by wind flow patterns, whereas wet deposition (WD) depended on precipitation in addition to wind flow patterns. The contribution of WD was approximately 50–90% of the total deposition, except during winter in Northern China (NCHN) and Eastern Russia (ERUS) because of the low amount of precipitation. The amount of PAH deposition showed clear seasonal variation and was high in winter and low in summer in downwind (South Korea, Japan) and oceanic-receptor regions. In the downwind region, the contributions from NCHN (WD 28–52%; DD 54–55%) and Central China (CCHN) (WD 43–65%; DD 33–38%) were large in winter, whereas self-contributions (WD 20–51%; DD 79–81%) were relatively high in summer. In the oceanic-receptor region, the deposition amount decreased with distance from the Asian continent. The amount of DD was strongly influenced by emissions from neighboring domains. The contributions of WD from NCHN (16–20%) and CCHN (28–35%) were large. The large contributions from China in summer to the downwind region were linked to vertical transport of PAHs over the Asian continent associated with convection.